Firm Value: The Influence of Tax Planning, Tax Avoidance, and Corporate Transparency - Hartono, Hartono; Trisnawati, Estralita; Verawati, Verawati (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to examine the effect of tax planning and tax avoidance on firm value and analyze information transparency as a moderating variable. Using data from 50 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period, the study generated 115 observations analyzed using panel data moderation regression with a fixed effects model. The results indicate that tax planning and tax avoidance do not significantly affect firm value individually, and information transparency does not moderate these relationships. However, simultaneously, tax planning and tax avoidance have a significant effect, reflecting an effective tax management strategy to enhance firm value. Additionally, other variables such as corporate governance, profitability, capital structure, and innovation have the potential to significantly influence firm value, warranting further research. This study contributes to the development of tax management and fiscal policy in Indonesia.